Connectedness among young adults in relation to intentions to help a suicidal peer - Nasriah Rizman Ali (2011)
The present study investigated connectedness among young adults in relation to their intentions to help a peer at-risk of suicide, in the context of a hypothetical scenario. Survey data was collected from 100 Singaporean university students aged between 19 to 26 years, from Asian ethnic backgrounds: Chinese, Malay, and Indian. The results show that young adults who are more connected overall to the multiple systems in the ecology are more willing to help a peer at-risk of suicide, even after accounting for the effects of controllability attributions. Connectedness in specific domains, such as family connectedness did not relate to helping intentions. The findings were discussed in relation to the current literature of connectedness and altruism. Implications of the findings include efforts to strengthen connectedness in young adults.